Is Active Representation an Organizational-Level Process? The Indirect Effect of Bureaucrats on Clients They Don't Directly Serve. Issue 1 (January 2018) - Favero, Nathan; Molina, Angel Luis
A now well-established link exists between passive representation of racial and gender minorities in certain bureaucracies and substantive benefits for the represented groups. However, few quantitative studies have distinguished between the multiple possible mechanisms by which passive representation might produce such effects. We conduct a novel set of empirical analyses aimed at determining whether or not passive representation produces effects only for those clients who directly interact with bureaucrats who share their demographic characteristics or if passive representation produces broader organizational-level effects. We find strong evidence that minority clients' outcomes are positively associated with representation in portions of the bureaucracy with which they do not directly interact. This suggests that either passive representation produces substantial bottom-up, organizational-level effects or that managers who recruit minority personnel also adopt policies that are favorable toward minority clients.